The Effect Of Project-Based Learning (PBL) On Iranian EFL Learners' Vocabulary Recall And Retention - Darastani, Azadeh Shafaei (2012)
This study explored the effectiveness of the Project-based Learning (PBL) method on vocabulary learning and acquisition of Iranian elementary EFL learners. PBL is an instructional method which involves students learning and facilitating their own projects. Working in collaboration with others, engaging in self-directed learning, applying new knowledge to solve problems, and reflecting on what has been learned are the main features of this method. PBL also incorporates real-life challenges where the focus is on authentic problems or questions and where solutions have the potential to be implemented. The study measured the effectiveness of PBL on EFL learners’ vocabulary recall and retention based on an experimental methodology. For this purpose, a pretest-treatment-posttest approach was employed on two groups of subjects, control and experimental. The former was taught new vocabulary items using the conventional teaching method while the experimental group was taught using PBL. To measure the effectiveness of PBL against the conventional method of learning vocabulary, post-tests and delayed post-tests were administered to both groups. The statistical analysis of the test scores shows that the experimental group scored better for recall and retention of new vocabulary. A survey on the students’ perceptions of PBL supports the findings on the significance of PBL. The survey reveals that students were satisfied with the new method of teaching and enjoyed the teamwork and their engagement with their classmates. The current research findings support the claim that learning and acquiring vocabulary knowledge should be done in context, through collaboration with other learners, and project work.